Faults and gas chimneys jointly dominate the gas hydrate accumulation in the Shenhu Area, northern South China Sea - Ren, Jinfeng; Cheng, Cong; Jiang, Tao; Kuang, Zenggui; Lai, Hongfei; Liang, Jinqiang; Chen, Zigui; Li, Tao (Frontiers in Marine Science, 2023)
Gas hydrates possess significant potential as an energy resource and exert a notable influence on global climate change. The Shenhu Area is one of the globally recognized focal points for gas hydrate research, and additional investigation is required to fully comprehend its gas migration mechanism. By utilizing the most recent core-log-seismic data and gas geochemical data, a comprehensive analysis was conducted to determine the influence of gas migration pathways on gas hydrate accumulation in the study area. This study investigated the various types of gas migration pathways, employing integrated geological models that incorporate faults and gas chimneys to understand their respective contributions to the accumulation of gas hydrates. Based on these findings and drilling constraints, a three-gas combined production model was subsequently proposed. Thermogenic gas, secondary microbial gas, and in situ microbial gas are all potential sources of the gas responsible for hydrate formation. Thermogenic gas plays a significant role in the gas hydrate system, as evidenced by distinct features of late-mature thermogenic gas observed in gas samples extracted from hydrates in Well W18. In the study area, the primary conduits for gas migration encompass deep faults, branch faults, and gas chimneys. Among these, deep faults act as the most crucial pathways of thermogenic gas migration. The integration of geological models that incorporating deep faults and gas chimneys has profoundly impacted the accumulation of gas hydrates in the Shenhu Area, consequently influencing the distribution of shallow gas and gas hydrate. Furthermore, the proposed three-gas combined production model, which involves the simultaneous extraction of deep gas reservoirs, shallow gas reservoirs, and gas hydrates, holds significant implications for exploring and developing deep-water natural gas resources. However, its successful implementation necessitates interdisciplinary collaboration among scientists.